Implementasi dan Pelatihan Agrowisata Virtual Tour dan Branding Pada Kelompok Tani Green Fresh Pelaga - IGKG Puritan Wijaya ADH; Ni Nyoman Utami Januhari; I Made Surya Adiputra; I Made Arya Budhi Saputra; I Made Bhaskara Gautama; I Gusti Ngurah Wikranta Arsa; Cahya Harya Dharma; Ni Putu Cindy Wulandari (Journal of Community Development, 2023)
Pelaga Village offers tourist attractions complete with their ecology. Pelaga Village has a large and diverse horticultural farm ranging from vegetables, flowers, and fruit. Pelaga Village has a Farmers Group called Pelaga Green Fresh with members spread throughout the Pelaga Village hamlets. Each member has a well-managed garden with the production of vegetable and fruit commodities. This potential makes Pelaga Village suitable as an agro-tourism location which is also one of the leading programs in the Pelaga Village RPJMDes. However, the Green Fresh Pelaga Farmer Group has not realized the potential of this agro-tourism due to a lack of knowledge and lack of information media to introduce the potential of this village. Therefore, branding and information media are needed so that the agro-tourism potential of Pelaga Village can be recognized by more people so that it can improve the welfare of the local community. In addition to using information media, the Green Fresh Pelaga Farmer Group also needs knowledge on how to brand and use this information media. This activity is carried out by creating information media in the form of a Virtual Tour which includes a garden atmosphere and agro-tourism video content. In addition, training was conducted on using the virtual tour website and socialization as well as training on Agro-tourism branding in the Pelaga village area, especially for the Pelaga Green Fresh Farmer Group. This is done to make the potential of Pelaga village more accessible and farmers understand about agro-tourism branding. Based on the results of the activity, members of the farmer groups have been able to understand the use of brands in the implementation of their products. In addition, the members of the Green Fresh farmer group also have a virtual tour website and are able to master the management of the virtual tour website.